Empowering young agri-entrepreneurs to invest in agriculture and food systems - (:unkn) unknown (My University, 2020)
Measures that empower young agri-entrepreneurs should be a key component of a sustainable development-centred investment promotion strategy. The very realization of future generations’ food security, the sustainable transformation of food systems and the combat against unemployment and distress migration all depend upon the successful implementation of strategies that make the agri-food sector more attractive for the youth. This, in turn, requires smart policy responses that will help young investors overcome the numerous barriers they face – access to finance, land, information and technical services, to name but the most crucial ones.Since 2017, FAO has provided support to African and South-East Asian countries in identifying key challenges for young agri-entrepreneurs and good practices through participatory capacity analyses and strategic planning processes which were carried out with, and for the youth.This report summarizes the main findings and lessons learned from FAO’s work with eleven African countries – Côte d’Ivoire, Guinea Conakry, Malawi, Mali, Mauritania, Mozambique, Namibia, Senegal, South Africa, Tunisia and Uganda. It identifies key challenges and policy recommendations regarding youth’s access to finance; land; technical services and information; as well as the engagement of youth in policy-making processes. The report also contains a set of five overall key policy recommendations for the empowerment of young agri-entrepreneurs.
Keywords: African Research